2014
DOI: 10.5539/mas.v8n2p160
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Economic Growth, Internet Usage and Publication Productivity: Comparison among ASEAN and World’s Best Countries

Abstract: Publication productivity, as measured by the number of papers, has been regarded as one of the main indicators of reputation of countries and institutions. Nevertheless, the relationship among research publications, economic growth and World Wide Web in ASEAN countries is still unclear. The main intention of this study was to identify publication productivity among ASEAN and the world's top ten countries in the last 16 years (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
(39 reference statements)
1
7
0
1
Order By: Relevance
“…Several bibliometric studies highlighted that citation counts are a function of many factors besides the scientific quality (Bornmann et al 2012), length of paper (Abt andGarfield 2002), visibility (Ale Ebrahim et al 2014), optimize scholarly literature for academic search engines (Beel, Gipp, and Wilde 2010), add the name of study in the title of all publications (Farhadi, Salehi, Embi, et al 2013), gross domestic product (GDP) (Gholizadeh et al 2014), number of authors (Krause 2009), self-archiving (Gargouri et al 2010 considered. The association between the number of references (independent variable) and time cited per year (dependent variable) of highly cited review papers investigated with linear and nonlinear models.…”
Section: Introductionmentioning
confidence: 99%
“…Several bibliometric studies highlighted that citation counts are a function of many factors besides the scientific quality (Bornmann et al 2012), length of paper (Abt andGarfield 2002), visibility (Ale Ebrahim et al 2014), optimize scholarly literature for academic search engines (Beel, Gipp, and Wilde 2010), add the name of study in the title of all publications (Farhadi, Salehi, Embi, et al 2013), gross domestic product (GDP) (Gholizadeh et al 2014), number of authors (Krause 2009), self-archiving (Gargouri et al 2010 considered. The association between the number of references (independent variable) and time cited per year (dependent variable) of highly cited review papers investigated with linear and nonlinear models.…”
Section: Introductionmentioning
confidence: 99%
“…In the short run, only with secure internet server per 1 million and mobile cellular subscription per 100 people resulted in positive and significant impact on economic growth. Gholizadeh et al (2014) studied the relationship between gross domestic product (GDP) and internet use in some ASEAN countries during 1996-2011. They found that there was a positive and significant association between internet use and GDP, although there were differences between those ASEAN countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Gholizadeh et al. (2014) studied the relationship between gross domestic product (GDP) and internet use in some ASEAN countries during 1996–2011.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teknologi internet tidak hanya berdampak pada pertumbuhan ekonomi, tetapi juga mempengaruhi belanja pemerintah bidang research and development (Choi & Yi, 2017). Penelitian empiris yang dilakukan oleh Gholizadeh et al (2014) dengan kasus sejumlah negara ASEAN juga menyimpulkan terdapat hubungan timbal balik antara pertumbuhan ekonomi dan penggunaan internet dikalangan masyarakat.…”
Section: Keterkaitan Antara Teknologi Informasi Dan Pertumbuhan Ekonomiunclassified